Education of farm children - Conway, A.G.; O'Hara, P. (Economic & Social Studies, 1986)
In this paper we examined educational participation by farm children, from two small areas in the West of Ireland. There has been a dramatic increase in participation, especially since the introduction of free post-primary education in 1967. This reflects the changing ability of parents to afford education for their children. Participation on smaller farms was lower than on larger farms up to 1967, but since that time it has almost equalised. Differences between those from smaller as compared to larger farms up to 1967 reflected the relative ability of parents to afford education. The pattern since 1967 shows how public policy can bring about equalisation of opportunities between families. Differences associated with children's occupations still persist. Non-farming daughters had more education than non-farming sons, who are more concentrated in manual occupations which have lower formal education requirements. In attempting to ensure access to occupations parents give daughters more education. Sons entering farming had least education but their access to farming is assured by gift or inheritance. The differential allocation of education reflects the efforts of parents to equalise occupational opportunities among their children.
Keywords: Education - Ireland; Farm children - education